Some conditions for finiteness and commutativity of rings. (1990) - Bell, Howard E.; Guerriero, Franco
Abstract : We present several new sufficient conditions for a ring to be finite; we give two conditions which for periodic ringsR imply thatR must be either finite or commutative; and we study commutativity in rings with only finitely many non-central subrings.